Challenges facing mobile banking services in reaching customers in Tanzania: A case of National Microfinance Bank (NMB) in Coastal region. - Biteya, A. (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirements for the award of degree of Masters of Business Administration in Corporate Management (MBA-CM) of Mzumbe University